Advances in Targeted and Systemic Therapy for Salivary Gland Carcinomas: Current Options and Future Directions. - Sreenivasan, Sushanth; Jiwani, Rahim A.; White, Richard; Bakalov, Veli; Moll, Ryan; Liput, Joseph; Greenberg, Larisa (Current Oncology, 2025)
Salivary gland carcinomas (SGCs) represent a rare and heterogeneous group of malignancies accounting for 3–6% of all head and neck cancers. While surgical resection and radiotherapy remain the standard for locoregional control, systemic treatment is indicated for recurrent or metastatic disease. Advances in molecular profiling have identified actionable targets such as NTRK gene fusions, HER2, immune checkpoint regulators, androgen receptors, and RET receptors. These have facilitated the development of targeted therapies, including TRK inhibitors, HER2-directed agents, and androgen receptor modulators, as well as emerging combinations of immunotherapy and chemotherapy. Despite these advancements, challenges such as resistance mechanisms and limited therapeutic efficacy persist. Overall response rates remain relatively low across most systemic therapies, reflecting a persistent unmet clinical need. This review discusses the current landscape of treatment options and explores promising clinical trials and future directions to enhance outcomes for patients with SGCs.